Shelf-lfife of fried potato chips using RBD palm olein, soybean oil and their blends - Che Man, Y.B.; Liu, J.L.; Abdul Rahman, R.; Jamilah, B. (Blackwell Publishing Inc.subscrip@blackwellpub.com, 1999)
Shelf-life of potato chips fried in refined, bleached and deodorized palm olein (RBDPO), soybean oil (SBO) and their blends was evaluated. Potato slices were fried for 130 s at 180 ± 5C at 30 min intervals over a period of 5 h/day for 5 consecutive days. Indicators of frying oil quality with the shelf-life of fried products chosen were total polar component and acid value. This study indicated that RBDPO was better than SBO for the preparation of fried potato chips in terms of shelf-life of products. The blends were also slightly better than SBO with increasing proportion of RBDPO. However, thé effects were minimal on the rate of development of rancidity in fried products beyond the fourth day of frying in the frying medium.